2020
DOI: 10.1093/nsr/nwaa110
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous changes in seed size, oil content and protein content driven by selection of SWEET homologues during soybean domestication

Abstract: Soybean accounts for more than half of the global production of oilseed and more than a quarter of the protein used globally for human food and animal feed. Soybean domestication involved parallel increases in seed size and oil content and a concomitant decrease in protein content. However, science has not yet discovered if these effects were due to selective pressure on a single gene or multiple genes. Here, resequencing data from over 800 genotypes revealed a strong selection during soybean domestication on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
139
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(160 citation statements)
references
References 52 publications
(42 reference statements)
2
139
4
Order By: Relevance
“…It should also be noted that, at the early maturation stage, GmSWEET39 exhibited decreasing gradients in expression in three connected layers of tissues, from the parenchyma (seed coat) to abaxial epidermis (cotyledon) and to aleurone ( Fig 2J and 2K ), which was coincident with the possible path of sugar flux from maternal seed coat to filial cotyledon [ 13 , 34 ]. Interestingly, we observed that the truncated GmSWEET39 (CC-) had a higher level of oil content, as evidenced by the H1 vs H2 comparison ( Fig 4A and 4B ) and supported by recent reports that overexpression of the truncated GmSWEET39 increased oil in seeds [ 28 , 29 ]. Previous studies have shown that replacing or removing the C-terminal peptide of sugar transporters significantly increased the transport activity by increasing the affinity for the substrates [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It should also be noted that, at the early maturation stage, GmSWEET39 exhibited decreasing gradients in expression in three connected layers of tissues, from the parenchyma (seed coat) to abaxial epidermis (cotyledon) and to aleurone ( Fig 2J and 2K ), which was coincident with the possible path of sugar flux from maternal seed coat to filial cotyledon [ 13 , 34 ]. Interestingly, we observed that the truncated GmSWEET39 (CC-) had a higher level of oil content, as evidenced by the H1 vs H2 comparison ( Fig 4A and 4B ) and supported by recent reports that overexpression of the truncated GmSWEET39 increased oil in seeds [ 28 , 29 ]. Previous studies have shown that replacing or removing the C-terminal peptide of sugar transporters significantly increased the transport activity by increasing the affinity for the substrates [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 89%
“…Here, we revealed that the complex and highly correlated protein and oil traits were controlled by a single gene GmSWEET39 with two major types of alleles carrying CC- and CC+ that were highly associated with high oil and high protein, respectively. Differing from the two contemporary studies locating GmSWEET39 using genetic sweep-inferred approach followed by functional validation [ 28 , 29 ], we identified GmSWEET39 and its causative allele (CC Indel) underlying the long-pursued chr15 QTL using the classic genetics and high-resolution GWAS followed by uncovering its dual role for oil and protein improvement. Uncovering the causative gene and alleles for the long-pursued chr15 QTL and the dual functions of the GmSWEET39 alleles allows us to associate it tightly with soybean decades’ breeding practices and highlight its importance in increasing oil or protein during soybean domestication and improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the numbers of the expressed genes that fell in the majority of those enriched terms were approximately doubled or tripled, such as hexose metabolic process (8 to 22), glycolysis (7 to 18) cellular nitrogen compound metabolic process (18 to 36), cellular amino acid biosynthetic process (15 to 32), Ribosomal proteins (47 to 132). It should be noted that no change in the numbers of the genes with the terms related to monolayer-surrounded lipid storage body (7), nutrient reservoir activity (11), and sulfur amino acid metabolic process (6 to 7) was observed, suggesting the importance of maintaining high transcript abundance of these genes for seed lling. Additional enriched GO terms for the 1,343 genes were identi ed, protein localization, glutamine family amino acid biosynthetic process, intracellular transport, gene silencing by RNA, vesicle-related components (COP-II-, COP-I, coated vesicle, transport vesicle, ER to Golgi transport vesicle, membrane-bounded vesicle).…”
Section: Genes With High Transcript Abundance During Seed Developmentmentioning
confidence: 99%
“…Thus far, several genes involved in seed nutrient accumulation such as bZIP123 involved lipid accumulation and GA20OX-associated seed weight and oil accumulation [8][9][10][11] and genes associated with seed development [12] have been identi ed. The conservation in some regulatory processes of seed development between soybean and model plant Arabidopsis was revealed [7,13].…”
Section: Introductionmentioning
confidence: 99%